Effectiveness of Foreign Exchange Market Intervention in Nigeria (1970-2013) - Dayyabu, Siba; Adnan, Ahmad Azrin; Sulong, Zunaidah (International Journal of Economics and Financial Issues, 2016)
The instability in the value of naira have made the Central Bank of Nigeria (CBN) a regular actor in the foreign exchange market in its efforts to stabilise the value of Naira and counter the disorderly behaviour of the market. This paper examines the effectiveness of the CBN’s intervention operations in the foreign exchange market using annual secondary time series data of four variables. The variables are the exchange rate, money supply, net foreign asset (a proxy for intervention variable), and lending rate ranging from 1970 to 2013. The result from the Johansen Juselius cointegration test shows that the naira exchange rate, intervention variable and monetary aggregates are cointegrated. The result from the ECM also indicates that the naira exchange rate will adjust and re-establish itself at the speed of 12% annually. Moreover, the result of the Granger causality test the CBN intervention is non-sterilised. Therefore, the CBN should provide an effective way through which its foreign exchange market intervention could be efficient and sterilised so as to ensure stability in the exchange rate and the price level. Keywords: Foreign Exchange Market, Nigeria, Exchange Rate JEL Classifications: E50; E52; E58; F31